TERMOFOSFATO MAGNESIANO E DISTRIBUIÇÃO VERTICAL DO FÓSFORO EM SOLOS COM DIFERENTES TEXTURAS - CRUZ, Yury Thalys Furtado; LOPES, Fernando de Souza; ROSSI, Ana Carolina Marinho; KUSANO, Daniel Makoto; CAMACHO, Marcos Antonio (ANAIS DO ENIC, 2018)
-